The Impact of the Implication of Balanced Scorecard Model (BSC) in Performance of the Post Company - Soleyman Iranzadeh; Sadegheh Hosseinzadeh Nojehdeh; Nahideh Najafi Emami (Problems and Perspectives in Management, 2017)
Balanced scorecard model is a method to evaluate and control programs with adequate consistency. According to it, a certain organization is evaluated and controlled in terms of financial aspect, together with growth and learning, internal business processes and customer aspects. This research is practical in purpose and a descriptive inferential method has been used to collect data in addition to utilizing five-scale Likert questionnaire. In order to increase the accuracy of the study, all 320 employees of post company have been under evaluation. A one-sample t-test has been used to analyze the questions of the study. Furthermore, Friedman test has been used to investigate the differences among groups. The results of testing the hypotheses indicate the effect of growth and learning of the employees of post company, as well as internal business processes, customer and financial aspects on the performance of the post company. Moreover, Friedman test probing the differences among groups shows that internal business processes and customer variables have the most significant impact upon the performance of the post company, while growth and learning and financial aspects have the least significant effect on the performance of the post company.